Effectiveness of DM Smart Ludo Educational Media on Knowledge and Blood Sugar Control in T2DM Patients in the Working Area of North Polombangkeng Health Center, Takalar Regency - Ilham, Rosmin; Zainuddin, Zainuddin; Suardi, Suardi (Poltekita: Jurnal Ilmu Kesehatan, 2024)
This study aimed to assess the effectiveness of DM Smart Ludo educational gaming media on knowledge and blood sugar control in type 2 diabetes mellitus (T2DM) patients in the working area of the North Polombangkeng Health Center, Takalar Regency, Indonesia. The research employed a quantitative, pre-experimental one-group pre-post test design with 33 T2DM patients selected through accidental sampling. Data were collected using a standardized questionnaire for knowledge assessment and observation sheets coupled with blood glucose level measurements for evaluating blood sugar control. The Wilcoxon test was used for statistical analysis with a significance level of p<0.05. The results showed a significant improvement in knowledge after the intervention, with the average score increasing from 6.52 to 12.06 (p=0.000). Blood sugar control also improved significantly, with the average blood glucose level decreasing from 287.30 mg/dL before the intervention to 214.09 mg/dL in the fourth week post-intervention (p=0.000). The percentage of respondents with normal blood sugar levels increased from 12.1% pre-intervention to 57.6% in the fourth week. In conclusion, the DM Smart Ludo educational gaming media significantly improved knowledge and blood sugar control in T2DM patients, highlighting the potential of game-based interventions in diabetes management. Further research with larger sample sizes and longer durations is recommended to confirm these findings.